Teenage parents and their children—position paper of the European academy of paediatrics and the European confederation of primary care paediatricians - Fontoura-Matias, José; Chakhunashvili, Davit George; Copley, Sian; Dembiński, Łukasz; Drosdzol-Cop, Agnieszka; Hadjipanayis, Adamos; Reali, Laura; Mazur, Artur (Frontiers in Pediatrics, 2024)
Addressing the multifaceted implications of teenage parenthood, this position paper by the European Academy of Paediatrics (EAP) and the European Confederation of Primary Care Paediatricians (ECPCP) delves into the complexities surrounding adolescent pregnancy and parenting. Despite a decrease in teenage pregnancy rates across Europe, the phenomenon continues to present significant challenges, impacting not only the adolescent parents but also their offspring and extended families. Key factors influencing teenage pregnancies include socioeconomic background, family structure, and access to sex education and contraception.The triad of mother, father and child presents individual distinct healthcare needs and vulnerabilities, highlighting the importance of specialised support and healthcare. This paper explores the psychological, social and educational repercussions of teenage parenthood on both parents and their children, including higher risks of postpartum depression, school dropout and repeat pregnancies. Furthermore, it underscores the critical role that paediatricians and primary care providers play in supporting these young families and advocates for comprehensive care models that address medical, psychological and socioeconomic needs.